A DRAFT CLASSIFICATION OF ATTRIBUTES IN KOREAN AND POLISH LANGUAGES - BOROWIAK, Anna (International Journal of Korean Humanities and Social Sciences, 2017)
Analyzing various classifications of sentence parts in Korean and Polish, it is easy to identify the existence of attributes in both of them, although the English term itself is not actually being used by Korean linguists, and thus might not be well known. Nevertheless, since the function of gwanhyeongeo (Kor. 관형어) in Korean, and attributes in Polish is similar, for the sake of transparency, this particular term will be used. The aim of this article is to propose a comprehensive classification of attributes in both target languages based on formal, syntactic and semantic parameters. In order to do it in the most exhaustive way, firstly different approaches concerning the definition of attributes, as well as the methods of their classification, proposed by various linguists in both languages will be examined. The author hopes to find out to which extent the typological differences between Korean and Polish are reflected in the attributes’ properties, according to which they can be classified.